Exploring EFL students’ motivation in essay writing through writing beliefs, self-efficacy, and attitudes: a case from Papua, Indonesia - Abel Yohanis Romrome; Concilianus Laos Mbato (Journal on English as a Foreign Language, 2023)
Although writing motivation has been widely investigated, limited research has focused on the three elements of internal motivation: writing beliefs, self-efficacy, and attitudes, let alone in the Papuan context. This study explored 32 Papuan EFL undergraduate students' internal motivation in essay writing through a purposive sampling technique. This research adopted a mixed method of quantitative and qualitative data. In collecting the quantitative data, a questionnaire was distributed through the Google Forms platform and analyzed using SPSS 26.0. Meanwhile, semi-structured interviews were conducted to gain qualitative data and analyzed by reading the data transcription and listening to the data recording three times to gain more valid information about the students' internal motivation in writing. The findings revealed that most EFL students had realized the importance of writing (WB1; M=3.63). Some students also demonstrated self-efficacy as writers (SE1; M=3.67), while others still felt anxious during writing (SE4; 3.60). Furthermore, some participants had created a positive attitude toward writing, whereas others did not. This research offers pedagogical implications for the lecturers and educators to promote the importance of writing to their students, encourage them to increase their self-efficacy as writers, and create positive attitudes toward writing.